Analysis of accuracy of two different implant impression techniques: A comparative study - Bangar, Bhushan; Reddy, Sashi Deepth J.; Arif, Shaik Mohammed; Asopa, Vipul; Swarup, Siddharth; Kaur, Inderpreet B. (International journal of health sciences, 2022)
Background: Comparatively evaluate the accuracy of two different implant impression techniques. Materials & methods: For the present study, reference models used were an edentulous mandibular cast with four implant analogues in the anterior region and a metallic insert in the posterior. Two impression techniques were studied as followed: Group 1: Polyvinyl siloxane impressions (putty and light body) using stock metal tray, and Group 2: Polyether impressions (medium body) using stock metal tray. Connection of the impression posts was done to implant analogues with the screws tightened manually such that their flat surfaces were facing buccally. The longer impression posts were connected to the anterior analogues and shorter were connected to the posterior analogues. A self-calibration test was performed to determine the accuracy obtained by the single evaluator. Results: Mean error among the specimens of Group 1 was 0.0441 while mean error among the specimens of Group 2 was 0.0425 respectively. While comparing the mean error among the two study groups, non-significant results were obtained. Conclusion: From the above results, the authors concluded that both the impression techniques can be used with equal effectiveness in implant procedures.